2020
DOI: 10.1074/jbc.ra120.013222
|View full text |Cite
|
Sign up to set email alerts
|

TOR complex 2 (TORC2) signaling and the ESCRT machinery cooperate in the protection of plasma membrane integrity in yeast

Abstract: The endosomal sorting complexes required for transport (ESCRT) mediate evolutionarily conserved membrane remodeling processes. Here, we used budding yeast (Saccharomyces cerevisiae) to explore how the ESCRT machinery contributes to plasma membrane (PM) homeostasis. We found that in response to reduced membrane tension and inhibition of TOR complex 2 (TORC2), ESCRT-III/Vps4 assemblies form at the PM and help maintain membrane integrity. In turn, the growth of ESCRT mutants str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
(143 reference statements)
7
17
0
Order By: Relevance
“…We predicted that under dysfunction of ceramide synthesis, inactivation due to excessive phosphorylation of Orm1 and may also Orm2, which might be a more potent SPT inhibitor [18,35], could lead to overactivation of SPT, which in turn leads to an increase in intracellular LCBs and LCBPs, thereby causing cytotoxicity [36,37]. Therefore, it is expected that cells might prevent excessive phosphorylation of Orm1/2 through Ypk1 somehow to avoid such events, possibly through dephosphorylation of Orm1/ 2.…”
Section: Regulation Of the Sphingolipid Biosynthetic Pathwaymentioning
confidence: 99%
“…We predicted that under dysfunction of ceramide synthesis, inactivation due to excessive phosphorylation of Orm1 and may also Orm2, which might be a more potent SPT inhibitor [18,35], could lead to overactivation of SPT, which in turn leads to an increase in intracellular LCBs and LCBPs, thereby causing cytotoxicity [36,37]. Therefore, it is expected that cells might prevent excessive phosphorylation of Orm1/2 through Ypk1 somehow to avoid such events, possibly through dephosphorylation of Orm1/ 2.…”
Section: Regulation Of the Sphingolipid Biosynthetic Pathwaymentioning
confidence: 99%
“…ESCRT can contribute to the replicative lifespan by at least two scenarios that are not mutually exclusive. First, ESCRT-dependent plasma membrane repair may prevent cell lysis and extend the replicative lifespan through the ESCRT’s function in plasma membrane repair as established in human cells (11, 26) and recently suggested in yeast (27). Second, ESCRT-dependent vacuolar membrane repair may extend the replicative lifespan of budding yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, heat stress induces Ca 2+ influx and Ca 2+ /calmodulinmediated activation of the protein phosphatase calcineurin, which reverses Lag1 and Lac1 phosphorylation [58,59]. In addition, calcineurin activates ORM2 transcription [8] and represses Orm1/2 degradation via the EGAD pathway by promoting dephosphorylation of Orm1/2 either directly or indirectly [101]. The opposite roles of TORC2 and calcineurin were further demonstrated by the fact that deletion of the calcineurin regulatory subunit B restored phytoceramide levels in cells containing a temperature-sensitive allele of the TORC2 subunit TSC3 [59].…”
Section: Mcss In Sphingolipid Metabolismmentioning
confidence: 99%
“…Later studies reported that the ESCRT machinery is employed for membrane remodeling at other sides as well [110]. Schmidt et al showed that the ESCRT III complex and Vps4 are recruited to the PM to maintain membrane integrity, in response to reduced membrane tension and TORC2 inhibition [101]. Conversely, deletion of Vps4 causes hypersensitivity to PM stress, deregulated calcineurin signaling, and activation of TORC2 signaling as a counter measure to calcineurin-inhibited sphingolipid synthesis [101].…”
Section: Mcss In Sphingolipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation